2017
DOI: 10.1177/0333102417744361
|View full text |Cite
|
Sign up to set email alerts
|

Serial testing of the ICHD-3 beta diagnostic criteria for probable reversible cerebral vasoconstriction syndrome: A prospective validation study

Abstract: Objectives To serially test the International Classification of Headache Disorders (ICHD) 3rd edition beta version criteria for 6.7.3.1 probable reversible cerebral vasoconstriction syndrome (probable RCVS) in patients with thunderclap headache. Methods We prospectively screened consecutive patients with thunderclap headache who visited the Samsung Medical Center between October 2015 and March 2017. Patients were included in the analysis if they a) visited our hospital within 1 month after onset, b) completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The criteria for probable RCVS, in which the diagnosis is suspected but cerebral angiography is normal, was assessed prospectively in a single-center study recruiting 99 adult patients with thunderclap headache from a headache clinic or the emergency department. 13 Patients were administered standardized questionnaires at the initial visit, 2 weeks, and 1 to 3 months after the first visit. Serial imaging was performed as well.…”
Section: Diagnosismentioning
confidence: 99%
“…The criteria for probable RCVS, in which the diagnosis is suspected but cerebral angiography is normal, was assessed prospectively in a single-center study recruiting 99 adult patients with thunderclap headache from a headache clinic or the emergency department. 13 Patients were administered standardized questionnaires at the initial visit, 2 weeks, and 1 to 3 months after the first visit. Serial imaging was performed as well.…”
Section: Diagnosismentioning
confidence: 99%
“…Reversible cerebral vasoconstriction syndrome (RCVS) is an under‐recognized neuroradiological disorder in which patients suffer abrupt severe headaches, often characterized as thunderclap headaches, and exhibit reversible cerebral vasoconstrictions . The clinical features of RCVS have been well characterized in studies involving, collectively, hundreds of patients worldwide . Patients with RCVS are at risk of severe complications including posterior reversible encephalopathy syndrome, ischemic stroke, and intracranial hemorrhage (including cortical subarachnoid, intracerebral, and subdural hemorrhage) .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The clinical features of RCVS have been well characterized in studies involving, collectively, hundreds of patients worldwide. [5][6][7][8][9][10][11][12][13] Patients with RCVS are at risk of severe complications including posterior reversible encephalopathy syndrome, ischemic stroke, and intracranial hemorrhage (including cortical subarachnoid, intracerebral, and subdural hemorrhage). [5][6][7][8][9][10]14 Sympathetic overactivity, 15 oxidative stress, 16 an impaired endothelial repair capacity, 17 and genetic predisposition 18 may contribute to the dysregulated vascular tone of cerebral arteries in RCVS, 4,19,20 though a definitive pathogenesis has not yet been delineated.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is lack of direct evidence to support this speculation. RCVS often cannot be diagnosed initially, since an angiogram performed in the early stage of RCVS can be normal (22,33,55,56) or is further considered as probable RCVS based on the ICHD-3 criteria (1,27). Studies have also suggested that even without significant angiographic vasoconstrictions, recurrent thunderclap headaches were almost diagnostic of RCVS (26,(57)(58)(59).…”
Section: Introductionmentioning
confidence: 99%